Curcumin attenuates the release of pro-inflammatory cytokines in lipopolysaccharide-stimulated BV2 microglia - Jin Cheng-yun; Lee Jae-dong; Park Cheol; Choi Yung hyun; Kim Gi-young (Acta Pharmacologica Sinica, 2016)
Aim: Pro-inflammatory mediators, such as prostaglandin E2 (PGE2) and nitric oxide (NO), and pro-inflammatory cytokines such as interleukin (IL)-1beta, IL-6, and TNF-alpha, play pivotal roles in brain injuries. The anti-inflammatory properties are known to be associated with significant reductions in pro-inflammatory mediators in brain injuries. In the present study we investigate whether the effects of curcumin on the production of pro-inflammatory mediators in lipopolysaccharide (LPS)-stimulated BV2 microglia. Methods: Curcumin were administered and their effects on LPS-induced pro-inflammatory mediators were monitored by Western blotting and RT-PCR. Result: Curcumin significantly inhibited the release of NO, PGE2, and pro-inflammatory cytokines in a dose-dependent manner. Curcumin also attenuated the expressions of inducible NO synthase and cyclooxygenase-2 mRNA and protein levels. Moreover, curcumin suppressed NF-kappaB activation via the translocation of p65 into the nucleus. Our data also indicate that curcumin exerts anti-inflammatory properties by suppressing the transcription of proinflammatory cytokine genes through the NF-kappaB signaling pathway. Conclusion: Anti-inflammatory properties of curcumin may be useful for treating the inflammatory and deleterious effects of microglial activation in response to LPS stimulation.